Research on Gender Narratives in Pop Music Variety Shows (Journal of humanities and social sciences exploratio, 2025)
With the changes in the cultural context of contemporary youth, gender concepts and patterns of intimate relationships have shown significant daily and diversified characteristics in popular music. As music variety shows with wide dissemination power, "The Summer of Bands", "Rap of China" and "Our Folk Songs" have collectively presented the cultural attitudes of contemporary youth towards gender awareness, emotional expression and relationship understanding in different styles. This study took all the lyrics of three programs as the corpus and conducted word frequency statistics, open coding and matrix query through NVivo to systematically analyze the two themes of "Gender Equality and Female Development" and "Diversification of Intimate Relationship Patterns". The results show that in the overall corpus, all three styles present a common trend of enhanced female subjectivity, flexible masculinity, and reciprocal intimate relationships. In terms of style differences, rock and roll place more emphasis on gender equality and subjective consciousness, while folk and rap stress more on life-like emotional experiences and relationship negotiations. This study reveals the thematic logic and style path of gender narratives in contemporary popular music, providing a new perspective for understanding gender culture in musical texts.
Keywords: Pop music; Gender narrative; Music variety show